THE VALUE OF MAGNETIC RESONANCE IMAGING AS COMPARED TO LAPAROSCOPY FOR THE DETECTION OF ENDOMETRIOSIS: Life Science-Radiology Science - ZADE MODARES, SHAHRZAD; MOTEVASSELIAN, MAHTAB; NAEIJI, ZAHRA; BAHRAMZADE, SARA; AMIRNAZARI, BEHNAZ; SANEI TAHERI, MORTEZA (International Journal of Life Science and Pharma Research, 2019)
The objective of the study is to determine the value of MRI for detecting Endometriosis by considering the main determinants of diagnostic accuracy which are essential to minimize false positive and false negative diagnoses. The present study aims to assess the diagnostic value of MRI as a standard reference to detect endometriosis as compared to the laparoscopic findings. According to the opinion given by a panel of experts, forty consecutive patients with complaints of chronic pelvic pain, infertility, dysmenorrhea, dyspareunia, cyclic hematuria, pelvic pain between menstrual cycles and corresponding gastrointestinal symptoms, were referred to the Radiology department for further evaluation. The MRI examinations were performed with a 1.5- T unit. After MRI, the patients underwent laparoscopy within a maximum interval of 10 days as the reference standard. Data was analysis by SPSS. Sixteen patients underwent normal laparoscopy and normal MRI without any endometriotic lesions. In the other 16 patients, laparoscopy could identify 24 sites of endometriosis (20 endometriomas, 3 in posterior cul-desac, 1 in trigon of bladder). 20 out of these 24 sites (83.3%) were reported in their MRI. It is evident that the MRI had a sensitivity, specificity, PPV, NPV, and accuracy of 93.7%, 100%, 100%, 94.1%, and 96.8%, respectively for the diagnosis of Endometriosis. MRI with its high sensitivity and specificity can be considered as a high reproducible tool to explore Endometriosis.